A Dog with Pseudo-Addison Disease Associated with Trichuris vulpis Infection. (8th June 2011) - Venco, Luigi; Valenti, Valentina; Genchi, Marco; Grandi, Giulio
Abstract : A female Rottweiler dog was presented with a history of intermittent vomiting and diarrhoea, dysorexia, weakness, and weight loss. Haemocytometry and biochemistry values were within normal ranges except for electrolyte analyses, that demonstrated hyponatremia and hyperkalemia with a decreased sodium/potassium ratio. A diagnosis of hypoadrenocorticism was suspected. Basal and post-ACTH stimulation cortisolemia were within the normal values. Electrocardiography was normal, and thoracic radiography showed no significant modifications. On abdominal ultrasonography, adrenal glands appeared normal, while the bowel was distended, and several thin linear hyperechoic objects floating in the lumen were observed. Two adult female whipworms ( Trichuris vulpis ) were collected following bowel irrigation. Anthelmintic treatment against the parasite was curative.